2010
DOI: 10.1208/s12249-010-9386-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sodium Caprate on Intestine Absorption and Antidiabetic Action of Berberine

Abstract: Abstract. Berberine, a plant alkaloid used in traditional Chinese medicine, has a wide spectrum of pharmacological actions, but the poor bioavailability limits its clinical use. The present aim was to observe the effects of sodium caprate on the intestinal absorption and antidiabetic action of berberine. The in situ, in vitro, and in vivo models were used to observe the effect of sodium caprate on the intestinal absorption of berberine. Intestinal mucosa morphology was measured to evaluate the toxic effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…Although hypoglycemic effect of BER is so enticing, it has not yet been used clinically as an anti-diabetic drug, mainly because of its low bioavailability (<5%) (Maeng et al, 2002). We also observed its poor intestinal absorption in vivo and in vitro in our previous study (Lv et al, 2010). As a result, BER has to be administered repeatedly and at high doses (1500–2000 mg/d) when used in diabetic patients (Yin et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although hypoglycemic effect of BER is so enticing, it has not yet been used clinically as an anti-diabetic drug, mainly because of its low bioavailability (<5%) (Maeng et al, 2002). We also observed its poor intestinal absorption in vivo and in vitro in our previous study (Lv et al, 2010). As a result, BER has to be administered repeatedly and at high doses (1500–2000 mg/d) when used in diabetic patients (Yin et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…It increases the paracellular permeability through enlarging the tight junctions, and then expanding paracellular routes for water-soluble, low lipophilic, and poorly absorbable drugs. Our previous data showed that sodium caprate could significantly increase the bioavailability of BER without any serious mucosal damage (Lv et al, 2010). In this study, we investigated whether co-administration of sodium caprate would alter the hypoglycemic effect of BER in diabetes mellitus in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium caprate is a medium chain fatty acid that promotes the absorption of poorly absorbable drugs by increasing the permeability of intestinal epithelium and by inhibiting the function of P-gp [116]. In the presence of sodium caprate, the absorption rate of BBR in the small intestine increases, leading to higher plasma levels of BBR and to a stronger hypoglycemic effect in diabetic rats (Table 5) [116; 117].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Strategies to improve the absorption and efficacy of BBR have been investigated in other studies such as the combination with sodium caprate. 27,28 The abnormal immune status in db/db mice, which directly leads to the lack of islet function, may be systemically improved by BBR, thus facilitating islet regeneration, while the independent effect of lipid nanoparticles in regulating insulin and other lipoproteins should also be considered. Additionally, the carrier materials, mainly including lecithin and tripalmitin, did not show toxic side effects in the experimental or pathological examination.…”
Section: Hypoglycemic Effect Of Bbr-slnmentioning
confidence: 99%